UMPSA Kilau Volunteer Squad extends aid to Putra Heights gas pipeline fire victims - Naqiah, Puaad (UMPSA, 2025)
KUALA LUMPUR, 4 April 2025 – The Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Kilau volunteer squad recently went to Putra Heights Mosque, which has been designated as the Putra Heights Temporary Relief Centre (PPS) for victims of the gas leak fire incident.